2021
DOI: 10.1111/jvim.16269
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods to monitor dogs with hypercortisolism treated with trilostane

Abstract: Background The use of adrenocorticotropic hormone stimulation test as method to monitor efficacy of trilostane treatment of hypercortisolism (HC) in dogs has been questioned. Objectives To evaluate and compare 12 methods with which to monitor efficacy of trilostane treatment in dogs with HC. Animals Forty‐five client‐owned dogs with HC treated with trilostane q12h. Methods Prospective cross‐sectional observational study. The dogs were categorized as well‐controlled, undercontrolled, and unwell through a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…However, the haptoglobin level has been reported to decrease during trilostane treatment [27][28][29]. Another recent study of dogs with HC reported that haptoglobin is significantly associated with clinical scores [21]. During this study, the immune intensity of haptoglobin did not clearly alter based on the HC conditions, but the carbonylated haptoglobin ratio was low in well-managed HC patients treated with trilostane.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, the haptoglobin level has been reported to decrease during trilostane treatment [27][28][29]. Another recent study of dogs with HC reported that haptoglobin is significantly associated with clinical scores [21]. During this study, the immune intensity of haptoglobin did not clearly alter based on the HC conditions, but the carbonylated haptoglobin ratio was low in well-managed HC patients treated with trilostane.…”
Section: Discussionmentioning
confidence: 58%
“…Our data suggest that protein carbonylation, which is one of the oxidative stress reactions, could be influenced by the medical control of HC. Although various methods have been considered for monitoring the health status after starting trilostane therapy, the gold standard has not yet been established for dogs with HC [19][20][21][22][23]. Additionally, the present results suggest that the carbonylation level of a 40-kDa protein could be a new factor used to monitor the medical condition of dogs with HC.…”
Section: Discussionmentioning
confidence: 82%
“…The UCCR is currently routinely used as a screening test for dogs with spontaneous hypercortisolism, 20 and few studies have investigated its performance in monitoring dogs with hypercortisolism on a trilostane or mitotane regimen. 21 , 22 , 23 , 24 , 25 , 26 However, the use of the UCCR has not been evaluated in diagnosing spontaneous HA.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to be mentioned that adrenal gland enlargement is not only observed in patients with cushing's syndrome, but as well in patients with primary hyperaldosteronism, pheochromocytoma, incidentaloma, acromegaly and sometimes in patients with severe chronic or acute diseases (pyometra, severe gastro-enteritis, glomerulonephritis, etc.). Because in this study low dose of trilostane was used as initial dosage, no dog showed any sign of hypoadrenocorticism and therefore no data is available on adrenal gland enlargement in alanine aminotransferase-ALT, gamma-glutamyl transferase-γGT) [16] with assessment of adrenal gland enlargement (together with clinical examination and endocrine tests) could as well be considered. Limitation of using abdominal ultrasound as a monitoring tool could be: demand for skilled sonographer and difficulties in obtaining measurements at the same position every time.…”
Section: Discussionmentioning
confidence: 99%